Optimizing packaging process efficiency and quality control at a black carbon manufacturer through lean six sigma and design of experiment - Bahauddin, Achmad; Trenggonowati, Dyah Lintang; Sonda, Atia; Yusuf, Vira Aleyda; Saeful Mutaqin, Ade Irman; Umyati, Ani (Universitas Sultan Ageng Tirtayasa, 2023)
CI is a multinational company that involves manufacturing carbon black. The carbon black is packed in a 1250 kg jumbo bag and a 25 kg paper sack. Based on reject weight data for December 2019, 4.4% of paper sacks were rejected, with some caused by suboptimal packer machine settings. The study will use the design of experiment to determine critical quality factors for carbon black grade Sterling-V, identify waste in the packaging process, determine the sigma value in the packaging process, identify factors causing product defects, evaluate the risk priority number, and provide suggestions for optimal packaging machine conditions through factorial experiments. The reject weight of Sterling-V products due to reject weight was 123 out of the total production. The study results showed a sigma level of 2.205, with the engine factor being the main cause of reject weight (RPN 900). The optimal packaging machine conditions proposed for Sterling-V grade are Bulk Fill Cut Off (22.5 kg), High Pressure Air (7 bar), and Trim Final Cut Off (25 kg), which can reduce reject weight to 23 from total production.